Perancangan Sistem Pengelola Inventaris berbasis Web menggunakan Framework MVC - Rinjani, Annisa; Munir, Sirojul (LPPM STT Terpadu Nurul Fikri, 2022)
Inventory Management System is an activity to record and borrow goods that runs manually at PT. Lima Titik Satu. A web-based inventory management system makes using a framework with the MVC method at PT. Lima Titik Satu to minimize the negative impact of a system still running manually. In building an inventory processing system, data was collected using the observation method, then analyzed and designed the system development using the waterfall method and UML diagrams to implement system development using the PHP framework Codeigniter with a MySQL database. The results of feature testing on the built system found that 93.21% of the inventory management system features can run well and use at PT. Lima Titik Satu.